(untitled) (Acta Scientiarum. Education, 2015)
In this article we undertake a study about the training process of the Roman soldier in the Epitoma rei militaris, document written during the last years of the fourth century a.D. We aim here to analyze the procedure reported by Vegetius view that aimed to to turn the recruit in soldier in the Roman army. We are supported in the concept of the Military Paideia, defining the process based on an ideal model of a soldier to problematize some essential points for the formation of the Roman soldier. We expect this work to develop an analysis of the elements of the Vegetius vision that they could form a Roman military matrix that would beat all the enemies.